The Challenges of the Malaria Elimination Program in the South East of Iran, a Qualitative Study - Khodamorad Soofi; Narges Khanjani; Fatemeh Kamiabi (Tehran University of Medical Sciences, 2018)
Background: Despite all the efforts made to control and eliminate malaria in Iran, this disease is still considered as a priority health problem in the South East of Iran. We aimed to determine the cultural obstacles which have prevented the elimination of malaria in this region. Method: This study was carried out through qualitative content analysis. Purposeful sampling was done from people who had malaria or were involved with malaria patients in 2015, in Sarbaz City, Sistan and Baluchestan Province, Eastern Iran. Data were collected through interviews using open questions and continued until data saturation. Results: The most important barriers in malaria prevention was delay in visiting health centers, delay in diagnosis and treatment due to superstitious beliefs, lack of information about the disease, misdiagnosis and fake doctors. Other obstacles were lack of trust and cooperation with interventions offered by the health system, lack of proper use of the available facilities to prevent malaria and commuting in the high-risk neighbor countries. Conclusion: Raising awareness in people, officials and health workers about malaria and preventive health interventions as well as health risks associated with fake doctors, following up and re-examination of peripheral blood smear in suspected cases, establishing malaria control stations in border areas and specific measures to refer immigrants and people crossing the border toward malaria diagnosis stations is suggested.